Correlation between Clinicopathology and Expression of Heat Shock Protein 72 and Glycoprotein 96 in Human Esophageal Squamous Cell Carcinoma. (1st March 2010) - Wang, Xiaoping; Wang, Qiaoxia; Lin, Huanping
Abstract : Heat shock protein 72 (HSP72) and glycoprotein 96 (gp96) are highly expressed in cancer tissues. Recent studies indicate the possible roles of HSP72 and gp96 in the development and progression of gastrointestinal carcinomas but detailed information is still ambiguous. We investigated the correlation between clinicopathology and expression of HSP72 and gp96 in human esophageal squamous cell carcinoma. The expression of HSP72 and gp96 was studied in 120 human esophageal squamous cell carcinomas with or without metastasis as well as in mucous membrane adjacent to cancers by way of immunohistochemistry. HSP72 immunoreactivities were detected in 112 of 120 primary tumors (93.3%) and in 30 of 120 mucous membranes adjacent to cancers (25.0%). Gp96 detected in esophageal squamous cell carcinoma and inmucous membrane adjacent to cancer was 85.0% and 20.0%, respectively. Both HSP72 and gp96 stained in cytoplasm. HSP72 and gp96 expression in esophageal squamous cell carcinomas withmetastasis was significantly higher than those with nonmetastasis (P < .05 ). The results indicate that there exists a significant correlation between the expression of HSP72 and gp96 and the progression of esophageal squamous cell carcinomas. HSP72 and gp96 expression were significantly associated with the presence of tumor infiltration, lymph node, and remote metastasis.